Daughters of the dust (Kino Video, 1999)
This film brings to life t he changing values, conflicts and struggles that confront everry family as they leave their homeland for the promise of a new and better future. it also explores the unique cultur of the Gullah people, descendants of slaves who lived in relative isolation on the sea Islands off the georgia coast.